Shared and unique transcriptional changes in the orbitofrontal cortex in psychiatric disorders and suicide - O'Donovan, Sinead; Ali, Suleiman; Deng, William; Patti, Gurnoor; Wang, Joshua; Eladawi, Mahmoud; Imami, Ali (Translation: The University of Toledo Journal of Medical Sciences, 2024)
Psychiatric disorders like major depressive disorder (MDD), schizophrenia (SCZ), and bipolar disorder (BPD), represent a significant global public health concern. Sex differences in the prevalence and presentation of psychiatric disorders, and the association of a psychiatric diagnosis with increased risk of suicide, are well-established. However, the neurobiology underlying these features of disease are not well understood. Dysfunction of the orbitofrontal cortex (OFC), a brain region responsible for decision-making and sensory processing, has been implicated in psychiatric disorders but remains understudied compared to other frontocortical brain regions. In this study we investigated sexual dimorphism in psychiatric illnesses and suicide by analyzing publicly available OFC transcriptional profiles (RNAseq data obtained from the Stanley Neuropathology Consortium) from individuals with SCZ, BPD, MDD, and non-psychiatric controls (n=15/group). Gene set enrichment analysis (GSEA) revealed significant differences in immune-related processes in male and female comparisons and in psychiatric disorders relative to controls. Analysis of top differentially expressed genes found changes in P2RY12 in males and females who died by suicide. Additionally, downregulation of protein folding processes was observed in female suicide subjects, suggesting an association between dysregulated protein metabolism and suicide. Our results further our understanding of the shared and unique molecular pathways underlying psychiatric disorders and suicide.